18x-7=11x-56

Simple and best practice solution for 18x-7=11x-56 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18x-7=11x-56 equation:


Simplifying
18x + -7 = 11x + -56

Reorder the terms:
-7 + 18x = 11x + -56

Reorder the terms:
-7 + 18x = -56 + 11x

Solving
-7 + 18x = -56 + 11x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11x' to each side of the equation.
-7 + 18x + -11x = -56 + 11x + -11x

Combine like terms: 18x + -11x = 7x
-7 + 7x = -56 + 11x + -11x

Combine like terms: 11x + -11x = 0
-7 + 7x = -56 + 0
-7 + 7x = -56

Add '7' to each side of the equation.
-7 + 7 + 7x = -56 + 7

Combine like terms: -7 + 7 = 0
0 + 7x = -56 + 7
7x = -56 + 7

Combine like terms: -56 + 7 = -49
7x = -49

Divide each side by '7'.
x = -7

Simplifying
x = -7

See similar equations:

| 90/x=9 | | X=2x+-2y | | 28-x=2 | | (7w^2+7-7w^5+3w)+(-5w^5-3w^2-9+9w)= | | 55x=40x+90 | | 6x=5x-13 | | 0.04-003x=0.4 | | 0.4-0.003x=0.4 | | y-10+x+30+2y=180 | | v^2+6v-45=0 | | -2x-2=9x+75 | | -3x+2=-7x-26 | | 0=x^4+26x^2+165 | | f(x)=x^2-5x+13 | | factorx^2+4-16=0 | | (3c)(8)(-8b)= | | a-b=b-a | | 3(3x-1)-(x-1)=6(x-10) | | 5x=1/2(x+5+31) | | 5x-8=7x-8 | | 6.8x+2=5.8 | | 6.5x+2=5.8 | | 1/2(3x-8)=x | | (X+3)=3(x-7) | | 1/2(x+3)-(x-3/2)=5x | | x=1/2(x-3+2x-5) | | -0.9x+7=-4.3(-0.9x+7)-6 | | 14x+18x-8+2=-2x+2-8 | | (x2)/(x4) | | 5c+7=-27 | | 9y-4x=7 | | 98+82+152+x=360 |

Equations solver categories